(untitled) (African Journal of Biomedical Research, 2023)
Despite global disability from traumatic spinal cord injury (TSCI) especially in Low-and-Middle-Income countries, there is dearth of literature on clinical profile and recovery pattern of its survivors. Hence, this study did this over a 2-year post-TSCI. Twenty-nine (20males) TSCI survivors who reported to tertiary health facilities within 6hours of injury between December 2018 and March 2020 were profiled within 24hours. TSCI-severity was assessed using American-Spinal Injury Association-scale; Functioning using Spinal Cord Independence-Measure, walking function using Walking-Index and neuro-muscular recovery using Neuromuscular Recovery-Scale, every 6-weeks for 6-months. Participants aged 15-58years (mean=36.75±11.75years; mode=35years). TSCI occurred most from Road-crash (65.5%) and among passengers of commercial vehicles (73.7%). It occurred more in cervical-spine (62.1%) resulting in quadriplegia/paresis, lumbar-spine (27.5%) and thoracic-spine (10.4%) causing paraplegia/paraparesis. More (31.0%) had ASIA-A and ASIA–C each, 24.2% had ASIA-B, while 13.8% had ASIA-D. Functional performance and Neuromuscular Recovery improved significantly (p<0.05) in all domains except open-with-key and sit-to-stand domains. Traumatic spinal cord injury is common in males of productive age and affects more cervical spine resulting in quadriplegia/quadriparesis. Individual with spinal cord injury had steady significant neuromotor and functional recovery over 6-month after the injury. Early and comprehensive Physiotherapy is key for functional recovery in TSCI.